The Influence of Prophylactic Calcium and Magnesium Supplementation on Postoperative Quality of Life and Hypocalcemia After Total Thyroidectomy: Study Protocol for a Randomized Controlled Trial - Tabriz, Navid; Fried, Dennis; Uslar, Verena; Weyhe, Dirk (Frontiers in Surgery, 2022)
Background: We want to investigate if a routine preoperative dietary supplementation of calcium and magnesium prior to thyroidectomy for nodular goiter and graves’ disease can influence patients’ outcome with regards to hypocalcemia associated symptoms and quality of life in order to reduce the risk of post-thyroidectomy hypocalcemia and to improve patient’s quality of life. Methods: The study will be conducted as a two-armed randomized controlled trial including patients scheduled for total thyroidectomy. Patients assigned to the intervention group will receive calcium carbonate and magnesium oxide starting 2 weeks preoperatively. Primary outcome is the postoperative quality of life measured by the ThyPRO-39 and EQ-5D questionnaires. Secondary outcome is the assessment of postoperative biochemical (calcium and PTH levels) and clinical hypocalcemia (symptoms as reported by the patient). Discussion: A prophylactic dietary supplementation with calcium and magnesium, which could easily be implemented in the preoperative setting, could potentially help to avoid or reduce hypocalcemia-associated symptoms and improve quality of life. In the event of a positive outcome, this preoperative procedure can be an inexpensive way to prepare patients scheduled for thyroidectomy and can possibly reduce disease-specific costs by reducing the postoperative complication rate. Trial registration: DRKS00017195 in the German clinical trials register (Deutsches Register Klinischer Studien, DRKS) on the 22.05.2019.